Pengaruh Ilustrasi Gambar pada Soal Geometri Bidang terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP - Pratiwi, Ni Putu Diah Ari; Ariawan, I Putu Wisna; Sariyasa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study was motivated by the low mathematical problem-solving ability of junior high school students, particularly in the topic of plane geometry. One contributing factor is student’s limited capacity to represent problems visually. The purpose of this research was to examine the effect of including pictorial illustrations in plane geometry problems on student’s mathematical problem-solving ability. The research employed a quasi-experimental method with a posttest-only control group design. The population consisted of 344 ninth-grade students of SMP Negeri 4 Singaraja, with the sample determined through cluster random sampling. Two classes were selected, namely class IX Cempaka (Group A) with 37 students and class IX Melati (Group B) with 34 students. Group A was given plane geometry problems with illustrations, while Group B received similar problems without illustrations. The main instrument used was an essay test, supported by a questionnaire as an additional instrument. The results showed that the average posttest score of Group A was 43.73, while Group B obtained 29.71. The independent samples t-test at a significance level of 0.05 produced a p-value of 0.000 (< 0.05), indicating a significant difference in problem-solving ability between the two groups. Furthermore, the effect size calculated using Cohen’s d was 1.99, categorized as a very high effect. This finding demonstrates that the inclusion of pictorial illustrations exerts a strong and meaningful influence on student’s mathematical problem-solving ability. It can be concluded that the absence of illustrations in plane geometry problems increases the level of difficulty students experience in solving them.